2018
DOI: 10.1111/1471-3802.12421
|View full text |Cite
|
Sign up to set email alerts
|

How are students on the autism spectrum affected by bullying? Perspectives of students and parents

Abstract: Previous research has focused on the prevalence of bullying of students with autism spectrum disorder (ASD), with little attention given to its emotional effect. This mixed methods study examined levels of worry about bullying and bullying experiences reported by students and parents. To determine whether some students with ASD are differentially affected, we explored associations between students’ characteristics (understanding of bullying, age and co‐morbid conditions) and their bullying experiences and worr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 38 publications
0
14
1
8
Order By: Relevance
“…More recently, studies have also examined cybervictimization in those with ASD, finding similarly high rates as those found in more traditional types of peer victimization. Further, cybervictimization was associated with depression and anxiety (Ashburner et al 2019;Kowalski and Fedina 2011;Wright and Wachs 2019).…”
Section: Prevalence Of Peer Victimizationmentioning
confidence: 95%
“…More recently, studies have also examined cybervictimization in those with ASD, finding similarly high rates as those found in more traditional types of peer victimization. Further, cybervictimization was associated with depression and anxiety (Ashburner et al 2019;Kowalski and Fedina 2011;Wright and Wachs 2019).…”
Section: Prevalence Of Peer Victimizationmentioning
confidence: 95%
“…It has been shown that students with disabilities are more likely to be victims and to have depressive symptoms due to this victimization ( Olivier et al, 2020 ). According to research with autistic students, they are highly concerned about the possibility of being victims and the reported rates of bullying suggest that they may be at disproportionate risk of psychological harm ( Ashburner et al, 2019 ; Gomes et al, 2020 ). When families in this study are asked about their concerns about the negative consequences of bullying on their children, the answers also include, among others, mental health issues, such as self-esteem, mental health, social participation, school attendance, academic performance, and behavior.…”
Section: Introductionmentioning
confidence: 99%
“…For individuals with and without IDD, experiences of bullying are related to a host of emotional problems, including anxiety, depression, low self‐esteem and aggressive behaviour (Adams, Fredstrom, Duncan, Holleb, & Bishop, ; Ashburner et al, ; Cappadocia, Weiss, & Pepler, ; Christensen, Fraynt, Neece, & Baker, ; Cook, Williams, Guerra, Kim, & Sadek, ; Hawker & Boulton, ; Masten et al, ; Schroeder, Cappadocia, Bebko, Pepler, & Weiss, ; Sebastian, Blakemore, & Charman, ; Singham et al, ; Sofronoff, Dark, & Stone, ; Storch et al, ; Swearer, Espelage, Vaillancourt, & Hymel, ; Zablotsky, Bradshaw, Anderson, & Law, ; Zeedyk, Rodriguez, Tipton, Baker, & Blacher, ). Youth with ASD are negatively impacted by bullying both in terms of their emotional and social well‐being (Ashburner et al, ; Humphrey & Symes, ; Zeedyk et al, ). Specifically, individuals with ASD who are bullied experience significantly more internalizing behaviour problems (e.g., depression, anxiety), poor social skills and more conflict with friends (Cappadocia et al, ; Zeedyk et al, ).…”
Section: Introductionmentioning
confidence: 99%